The Role Development of Civil Society Organization for Sustainable Artisanal-Fisheries Community Management: A Case Study of Ao-Udom Artisanal-Fisheries Community, Si Racha District, Chonburi Province - Kanjanawong , Danusorn; Sungkaew, Buchita (Suan Dusit Graduate School Academic Journal, 2022)
The result from the Laem Chabang Deep-Sea-Port Industry Development Project had an impact on the local fishermen’s occupation in Ao Udom area. Because of the constructions, it caused tidal changes, oil stains, garbage problems, resulting in a decrease in the number of marine animals and local fishing areas. In addition, noise and dust pollution affected people’s health in the community. Thus, civil society groups were formed to fight for the solutions of the social and environmental problems caused by that development activities. There were groups formed by members of the Ao Udom community and civil society groups outside the community that came to support the operation in 2 forms: 1) the official form, where representatives of civil society groups in the area were appointed to join the committee in the government sector to monitor the social and environmental impacts of the project and 2) semi-official form where the civil society groups in the area collaborated with the government agency and civil society groups outside the area to work together. Thus, the civil-society organizations played 5 roles in the development of artisanal-fisheries community: (1) Examining the state powers used by government agencies involving in artisanal-fisheries community, (2) Proposing the community’s demands through various channels, (3) Encouraging artisanal-fisheries community to gain and access to community rights, (4) Building the development networks for artisanal-fisheries community, and (5) Calling on the government to support the Enforcement of the Promotion and Development of Civil Society Organizations Bill B.E....to make the promotion of Thai civil-society role clearer.